PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATA PELAJARAN IPS MELALUI PENGGUNAAN MODEL PETA KONSEP (MIND MAPPING) PADA SISWA KELAS VII A SEMESTER GENAP SMP N 1 GISTING T.P. 2010/2011 - Masneli, Masneli (JURNAL TAPIS, 2014)
Social science is an important subject to be taught in the school because it has been designed to develop knowledge, insight, and critical thinking so that the students would be able to live in harmony in the misdt of the society. Nevertheless, the current teaching practice of social science is far from perfect since it consists only general explanation of a topic being taught. Consequently, the students tend to dislike social science. To cope with such, the researcher utilized the mind-mapping model to develop the teaching practice so that, in turn, the students would be better at doing the class activities. The research was conducted in State Senior High School 1 of Gisting district. The research itself was a classroom action research consisting of two cycles. The result of the research shows that the use of Mind-mapping model has helped the students of the school increase their grades as well as their involvement in the classroom activities.Keywords : social science learning, classroom activities, grades, mind-mapping model